Juozo Čiuldos gramatikos „Pratarmė“ - Jurgutis, Vytautas (Knygotyra, 1974)
J. Čiulda (1796–1861), the author of a work written in Polich language “Reflections on grammatical principles of the Samogithian language”, the “Introduction” to which is the object of this paper, was a student on the faculty of moral and political sciences of the Vilnius University (1818–1822), he studied there at the same time as S. Daukantas, J. Domeika, A. Mickiewicz, T. Zan. From 1823 to 1835 he thought in Kaunas, later and till the end of his life he was a catholic priest. J. Čiulda was interested in Greek, Roman, Polish and Lithuanian literature, Lithuanian folklore, in investigation of the Lithuanian language. His work on the grammar of this language J. Čiulda completed 1854 m., but it was not published and remains only in manuscript. “The Introduction” to the work of J. Čiulda is a valuable document of the Lithuanian culture. In his work the author depicts a vivid picture of the conditions of life of the age he lived, and explains his views on the Lithuanian language, its role in the education of people. The author affirms the antiquity, peculiarity, and richness of the Lithuanian language, which has been constantly preserved and perfected by the people. He requires a revision of the deeply rooted prejudice, that the Lithuanian language is fitted only for communication among common and ignorant people and is not able to express profound ideas. In author’s opinion, the care for the beauty and perfection of the mother tongue is a duty of every educated Lithuanian. His work J. Čiulda qualifies as an attempt; creation of a scientific grammar of the Lithuanian language has to become a task of many scientists.